Proactive Corporate Environmental Management Practices in Industrial Estate Multan, Pakistan - Ayub, Muhammad Kamran; Zaman, Khalid (International Review of Management and Marketing, 2015)
Industrial growth in Pakistan is leading towards an increased inclination for the adoption of corporate environment management. With the passage of time, more global environmental problems are becoming more obvious and hazardous. Progressing facilities have to be more proactive in environmental management and prefer taking voluntarily environmental actions for regulatory compliance. However, there are comparatively few researches have explored the motivation for adoption of proactive environmental management strategies (PEMS) especially for developing countries like Pakistan. The objective of this study is to assess the relevance of environmental management practices in the Multan Industrial Estate, Pakistan. Moreover, to identify the driving forces for adopting proactive environmental management was the objective of study. The standard questionnaire was devised to determine the drivers for proactive Corporate Environmental Management. The study conducted a survey of Multan Industrial Estate to assess the proactive environmental management strategies. The data was collected from 420 respondents and analyzed by sophisticated statistical techniques using SPSS. The results show that a large number of respondents agreed on the importance of environmental management and its driving forces for the adoption of PEMS. From the study, Regulatory pressure, cost factors, Competitive requirements, stakeholder forces were found as forces for the adoption of Environmental Management Practices. Importance of Environmental management had the highest mean in analysis. A significant relationship was found between all the driving forces for adoption of Environmental Management Practices. Importance of Environmental management was found to be highly correlated with Regulatory pressures. High internal consistency was also identified that shown the reliability of questionnaire. A number of studies supported the research results of the current study. This study valuable to both government officials and environmentalist to device sustainable polices for Pakistan. Keywords: Proactive environmental management practices; Regulatory pressure; cost factors; stakeholder forces; Industrial Estate Multan; Pakistan. JEL Classifications: C12; Q51